Gestational thrombocytopenia: a case–control study of over 3, 500 pregnancies. (9th June 2021) - Fogerty, Annemarie E.; Dzik, Walter
Summary: Gestational thrombocytopenia (GT) affects an estimated nine million women annually. Women with GT have recurrent episodes on subsequent pregnancies suggesting that GT is related to a maternal factor rather than a factor unique to the individual pregnancy. We performed a case–control study of over 3 500 pregnancies at a single hospital during 2017. We defined GT as any pregnancy with a platelet count <150 000/µl during the 100 days prior to delivery. We excluded women with platelet counts <50 000/µl or with conditions known to cause thrombocytopenia. GT was present in 12% of pregnancies. The median platelet count at delivery was 134 500/µl in cases versus 208 000/µl in controls, P < 0·0001. During the pregnancy, the platelet count declined 31·8% in cases compared with 18·3% in controls ( P < 0·0001) in association with a significant increase in mean platelet volume during each trimester. Among women with GT, platelet counts rapidly increased during the first week postpartum, consistent with a mechanism directly related to high blood flow rates in the gravid uterus. GT, a recurrent condition of at‐risk women, is a common haematological disorder of pregnancy. Future research may focus on genetic gain‐of‐function polymorphisms resulting in increased turnover of platelets uncovered only during periods of high‐shear blood flow.